Mischievous misbehaviours : a short for kids and adults alike - Cai, Lixian (2010)
A story about a mischievous little boy who gets his little buttock whacked and learns his lesson. The animation aims to conjure the festive, raucous mood of Chinese New Year, and at the same time tell a tale that is heart-warming and educational to young children.